POLIKLINIK GIGI UNTUK LAYANAN, PROMOSI DAN LOKASI TERHADAP KEPUASAN DAN LOYALITAS PASIEN - Dewi Hendrayanti; Rachmat, Basuki (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the influence of service quality, location, and promotion on patient satisfaction and loyalty at the East Perak Community Health Center in Surabaya. The study aims to determine the relationship between variables and the dominant factors influencing patient loyalty. The method used was a causal quantitative approach with a sample of 200 patients, data collection through a Likert-scale questionnaire, and analysis using SEM-PLS. The results showed that service quality, location, and promotion had a significant positive effect on patient satisfaction, while satisfaction had a positive effect on loyalty. Service quality was the most dominant factor. These findings support the development of strategies for continuously improving the quality of public health services for community health center management and increasing community satisfaction.